Lexical and Structural Ambiguities in the Headlines of The Nigerian Tribune and The Punch, 2015-2022 - Jolaoso, Oluwafemi; Azeez, Isiaq (Journal of Language and Literature Studies, 2024)
The primary goal of communication is information sharing for mutual understanding between the sender and the recipient. A news headline is a form of communication that serves as the gist of the main points in the lead. It is written in a more succinctly attention-grabbing manner. It makes the readers curious and piques their interest. However, some of the Nigerian newspaper headlines are ambiguous. They are open to two or more interpretations against the writer’s intended meaning. Therefore, this study investigated the lexical and structural ambiguity in the Nigerian newspapers: The Nigerian Tribune and The Punch. The use of Theory of Meaning by Ludwig Wittgenstein served as the theoretical framework for this study. The data were collected from The Nigerian Tribune and The Punch and qualitatively analysed. Ambiguous headlines were found and their interpretations were given, using the Use Theory of meaning. The study found that ambiguities are frequently used in newspaper headlines due to the polysemous nature of the lexical choices, the dual function of some parts of speech, indexical references and wrong places of prepositional phrases. The analysis showed that these phrases were not placed immediately after their antecedent and thus resulted in ambiguous headlines. The study concluded that headline writers should discontinue using too much ambiguity, to avoid discouraging the readers. The deck, kicker and rider should also be used along with the headlines. Also, the readers are encouraged to contextually study the contents to get the precise and intended message.